LONELINESS AND DEATH: THE PLIGHT OF THE ELDERLY Dr. Jaya Thoidingjam, Assistant professor Department of English, G. P. Women's College, DMU Dr.Th. Diana Devi, Assistant professor Department of Home Science, G. P. Women's College DMU Abstract Old people (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Old people are faced with numerous physical, psychological and social role changes that affect their sense of self and capacity to live happily. Many people experience loneliness and depression in old age, either as a result of living alone or due to lack of close family ties and connections. Literature can help to understand the elderly and the ageing process and to develop empathy for the people who are ageing. Literary worksportraying the lives of the elderly living in old-age homes make the plight of old people visible to the readers. These writings help people to understand the feelings of the elderly and to evoke in the readers a desire to look deeper into the feelings and aspirations of old people. There is need to write about the experiences of elderly people so that the huge distance that is seen between the older generation and the younger peoplecan be bridged. As such novels and poemsabout old people can make the readers see old age in a new way by taking the readers closer into their lives and their conditions.